Improving Arabic Reading Skills through Al-Wadlih Grammar Instruction in Islamic Boarding Schools - Nur Rohman; Syamfa Agny Anggara (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
Arabic reading skill is a central competency in Islamic boarding school education because it enables students to access classical Islamic texts and understand Arabic sources accurately. However, many students still experience difficulty applying grammatical knowledge to reading practice, even after learning basic rules of nahwu. This study examines the effectiveness of Al-Wadlih-based grammar instruction in improving Arabic reading skills among secondary-level students in Indonesian Islamic boarding schools. The study employed a quantitative experimental design involving second-grade secondary students at Mambaul Hikmah Islamic Boarding School in Tegal and Darussalam Islamic Boarding School in Brebes. The experimental groups received grammar instruction using selected materials from Al-Wadlih, while the control groups continued learning through the previously used grammar text. The intervention was conducted in eight meetings, each lasting 45 minutes, through opening activities, review, grammar explanation, guided exercises, and reading application. Data were collected through pre-tests, post-tests, observation, interviews, and questionnaires, and analyzed using descriptive statistics and t-test analysis. The findings show that Al-Wadlih-based instruction significantly improved students’ Arabic reading skills in both schools. At Mambaul Hikmah, the obtained t-value was 4.534, while at Darussalam the obtained t-value was 3.125; both exceeded the critical t-table values at the 0.05 and 0.01 significance levels. These results indicate that Al-Wadlih can function as an effective pedagogical bridge between grammar mastery and Arabic reading competence. The study contributes to Arabic language education by highlighting the importance of contextual, exercise-based, and reading-oriented grammar instruction in pesantren learning